Analisis Kualitas Website SMA Menggunakan Metode Webqual 4.0 - Widiyanto, Dimas Akhbar; Purnama, Benni; Mulyono, Herry (TIN: Terapan Informatika Nusantara, 2024)
SMA Negeri 10 is a senior high school in Jambi City. The SMA Negeri 10 website is used as a means to provide information to students or the general public who want to find information about SMA Negeri 10 Jambi City. the purpose of this research is to determine the ratings of website users, to measure the quality level of the website and find out the variables that influence user satisfaction on the website of SMA Negeri 10. the research method used is webqual using 4 variables namely usability quality, information quality, interaction quality and user satisfaction. data was taken by distributing offline questionnaires to student respondents in class X and XI and distributing online questionnaires (google form) to alumni class of 2023 with a total of 270 respondents to users of the SMA Negeri 10 Website, Jambi City. Data processing in this study used IBM SPSS statistics ver 25.0 software.The results of this study indicate that there are 2 variables that have a significant effect on the user satisfaction variable, namely the usability quality variable which also has the greatest influential value and interaction quality, while the other variable, namely information quality, does notsignificant effect on user satisfaction.